Radiation tolerant YAG: Ce scintillation crystals grown under reducing Ar+CO atmosphere - Dormenev, V.; Brinkmann, K.-T.; Borisevich, A.; Kazlou, D.; Korzhik, M.; Moritz, M.; Novotny, R.W.; Orsich, P.; Gerasymov, Ia; Tkachenko, S.; Arhipov, P.; Sidletskiy, O.; et al. (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2021)
The scintillation properties and radiation hardness of undoped and Ce doped YAG crystals, which were grown from tungsten crucibles in the Ar + CO atmosphere and annealed under different conditions, have been evaluated. The scintillation crystals obtained under such conditions have a high scintillation yield, demonstrate short scintillation kinetics with the major component of ∼60 ns, and demonstrate high radiation resistance when irradiated with both γ-quanta and high energy protons. The obtained results open up the opportunity to produce high-temperature garnet crystals using iridium-free technology, which forms the basis for a technology for mass production at an affordable price.